2021
DOI: 10.1097/md.0000000000026242
|View full text |Cite
|
Sign up to set email alerts
|

Transient oculomotor paralysis after cerebral angiography

Abstract: Rationale: A special case of transient oculomotor nerve palsy after cerebral angiography. Patient concerns: A 55-year-old man developed oculomotor nerve dysfunction after right radial artery puncture angiography. Diagnoses: Cerebral angiography-induced oculomotor nerve palsy. Interventions: According to the patient's disease state, intravenous drip of dexamethasone 10 mg/d. Outcomes: Mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It should be noted that not all CIE symptoms improve rapidly with treatment, particularly those related to nervous system damage, including visual disturbances, diplopia, and oculomotor dysfunction, which may be caused by optic and oculomotor nerve injury. Although most patients with CIE have a self-limited course and recover within 72 hours without sequelae, Qiu et al [19] reported a patient with CIE who required 19 days to recover after undergoing cerebral angiography. The case report by Leong et al [20] reported a patient who developed CIE after undergoing intracranial aneurysm coiling, and 1 year later, the patient still suffered from chronic left-sided limb spasticity and was diagnosed with irreversible CIE.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that not all CIE symptoms improve rapidly with treatment, particularly those related to nervous system damage, including visual disturbances, diplopia, and oculomotor dysfunction, which may be caused by optic and oculomotor nerve injury. Although most patients with CIE have a self-limited course and recover within 72 hours without sequelae, Qiu et al [19] reported a patient with CIE who required 19 days to recover after undergoing cerebral angiography. The case report by Leong et al [20] reported a patient who developed CIE after undergoing intracranial aneurysm coiling, and 1 year later, the patient still suffered from chronic left-sided limb spasticity and was diagnosed with irreversible CIE.…”
Section: Discussionmentioning
confidence: 99%